Communication Patterns of Content Creators in Local Wisdom-Based Tourism Development in North Sumatera - Muhammad Alfikri; Zulkarnaen Zulkarnaen (Borong Newinera Publisher, 2025)
This study aims to explore the communication patterns applied by content creators in developing local wisdom-based tourism in North Sumatera, an important approach in promoting the uniqueness and diversity of regional culture. Although local wisdom has great potential as a tourist attraction, efforts to optimize it in digital marketing are still limited. This study uses a qualitative approach with an in-depth interview method with several local content creators to understand the communication strategies they use, including how local values are incorporated into the narratives and visuals presented. The results of the study show that content creators can utilize local wisdom to create interesting and authentic content, build emotional connections with audiences, and strengthen the image of the destination. The conclusion of this study confirms that local wisdom-based communication by content creators not only increases tourist attractions but also supports the sustainability of tourism in North Sumatera.